2004
DOI: 10.1073/pnas.0307982101
|View full text |Cite
|
Sign up to set email alerts
|

Polyandry in a marine turtle: Females make the best of a bad job

Abstract: The female perspective on reproductive strategies remains one of the most active areas of debate in biology. Even though a single mating is often sufficient to satisfy the fertilization needs of most females and the act of further mating incurs costs, multiple paternity within broods or clutches is a common observation in nature. Direct or indirect advantage to females is the most popular explanation. However, the ubiquity of this explanation is being challenged by an increasing number of cases for which benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
151
3
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(164 citation statements)
references
References 58 publications
9
151
3
1
Order By: Relevance
“…Hence, we found no evidence of improved fitness in the offspring when sired by a primary father (male who gives greater proportion of the offspring) compared to any other secondary fathers. Similar results were concluded in Lee and Hays (2004) study.…”
Section: Fitnesssupporting
confidence: 91%
“…Hence, we found no evidence of improved fitness in the offspring when sired by a primary father (male who gives greater proportion of the offspring) compared to any other secondary fathers. Similar results were concluded in Lee and Hays (2004) study.…”
Section: Fitnesssupporting
confidence: 91%
“…Hence, we found 392 no evidence of improved fitness in the offspring when sired by a primary father (male who gives 393 greater proportion of the offspring) compared to any other secondary fathers. Similar results were 394 concluded in Lee and Hays (2004) study. 395 In this study, measurements of morphological traits (crawling speed, length and weight) were taken 396 following the same procedure.…”
Section: Laboratory Analysissupporting
confidence: 83%
“…While some 41 authors have argued that its prevalence is intriguing, due to the energetic fitness costs that such 42 behaviour incurs (Lee & Hays, 2004;Bilde et al, 2009), others have demonstrated how females may 43 gain indirect genetic benefits to offset the cost by mating with multiple males (Byrne & Roberts, 2000; 44 LaBrecque et al, 2014). For example, polyandry may provide genetic benefits by improving the 45 chance that females will acquire "good" genes or by enhancing the genetic diversity of their progeny 46 (Yasui, 1997 (Packer et al, 1991;Craighead et al, 1995;Keane, Dittus & Melnick, 1997;FitzSimmons, 1998; Uller 51 & Olsson, 2008) and enabling investigation into the genetic consequences of multiple matings.…”
Section: Alfaro-núñezmentioning
confidence: 99%
See 1 more Smart Citation
“…Confronted with the potential costs of multiple mating, the risk of disease transmission, predation, energetic loss and costs resulting from harmful male adaptations (Andersson 1994;Byrne & Roberts 1999;Thrall et al 2000), many hypotheses have been proposed to explain why females mate multiply (Reynolds 1996;Jennions & Petrie 2000;Eberhard & Cordero 2003). First, these females may not retain complete control over mating or they may avoid the cost of resistance to male harassment (Thornhill 1980;Lee & Hays 2004). Second, females may obtain direct benefits from multiple mating, which extends from the supply of sufficient fertile sperm (assurance of fertilization; Sheldon 1994) to any form of paternal investment, such as parental care, nuptial gifts or sperm nutrients (Davies 1992;Andersson 1994).…”
Section: Introductionmentioning
confidence: 99%